System kształcenia i doskonalenia nauczycieli w Singapurze. Między utopijną wizją a rzeczywistością - Kwiatkowski , Stefan T.; Nowosad, Inetta (Studia Edukacyjne, 2018)
Starting from the concept of utopia, the article focuses itself on the analysis of teacher education and professional development system that has evolved in Singapore over the last few decades. On the wider background of this particular model’s elements, a description of the institutions responsible for teacher continuing education, established to prepare them to the fundamental task they are meant to perform in the modern knowledge society, has been provided.